2021
DOI: 10.3390/genes12091456
|View full text |Cite
|
Sign up to set email alerts
|

CpBBX19, a B-Box Transcription Factor Gene of Chimonanthus praecox, Improves Salt and Drought Tolerance in Arabidopsis

Abstract: Zinc-finger proteins are important transcription factors in plants, responding to adversity and regulating the growth and development of plants. However, the roles of the BBX gene family of zinc-finger proteins in wintersweet (Chimonanthus praecox) have yet to be elucidated. In this study, a group IV subfamily BBX gene, CpBBX19, was identified and isolated from wintersweet. Quantitative real-time PCR (qRT-PCR) analyses revealed that CpBBX19 was expressed in all tissues and that expression was highest in cotyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…A series of TFs have been reported to function during cold signal perception, transduction and response processes. Among these TFs, BBX family members are of great importance in plant cold stress responses in Arabidopsis, apple, rice, and wintersweet (C. F. Li et al ., 2021; Wu et al ., 2021). MdBBX20 can respond to low temperatures, thereby promoting anthocyanin accumulation (Fang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A series of TFs have been reported to function during cold signal perception, transduction and response processes. Among these TFs, BBX family members are of great importance in plant cold stress responses in Arabidopsis, apple, rice, and wintersweet (C. F. Li et al ., 2021; Wu et al ., 2021). MdBBX20 can respond to low temperatures, thereby promoting anthocyanin accumulation (Fang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, six CsBBX genes displayed variations in expression under salt stress according to RNA-seq and qRT-PCR results (Figures 6B and 8), indicating that CsBBX genes might play crucial roles in response to salt stress. Wintersweet (Chimonanthus praecox) CpBBX19 was upregulated by four types of abiotic stress (heat, cold, salt, and drought), and overexpression of CpBBX19 promoted salt and drought stress tolerance in transgenic Arabidopsis plants [58]. In addition, qRT-PCR results showed that five out of the six selected CsBBX genes were differentially expressed under cold stress (Figure 7), suggesting that CsBBX genes might also participate in response to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor (TF), also known as trans-acting factors, are a type of protein molecules that can specifically bind to cis-acting elements in the promoter region of eukaryotic genes to ensure that the target gene is expressed at a specific intensity at a specific time and place ( Wu et al, 2021 ). Under the stress condition, the transcription factor associated with stress tolerance can regulate the expression of anti-retroviral motifs and transmit the stress signal, and the signal can be involved in the information transmission can be cascaded so that, the transcription factor can be used to improve the resistance of plants ( Wang et al, 2020 ).…”
Section: Cotton Adversity Stress Transcription Factor Genementioning
confidence: 99%